Examining EFL vocational school teacher resilience in the Chinese context: a structural equation modeling approach - Duan, Siyu; Cui, Jianli; Li, Xiaoxue; Wang, Fangliang; Xia, Miaoyue (Frontiers in Psychology, 2025)
Teacher resilience has recently received significant attention in psychology and general education. However, the research on English as a foreign language (EFL) teacher resilience, particularly among vocational school teachers, has been understudied. There is still a lack of exploration regarding the internal structure of EFL vocational school teacher resilience in the Chinese context. To address this gap, this study employed a structural equation modeling approach to investigate the structure of resilience among EFL vocational school teachers. The EFL Teacher Resilience Scale was completed by 265 Chinese EFL vocational school teachers. Confirmatory factor analysis revealed a tri-dimensional structure of EFL vocational school teacher resilience involving professional, emotional and social and cultural dimensions. Additionally, the findings of this research indicated a significantly high level of EFL vocational school teacher resilience, both overall and across its three dimensions. These findings provided implications for the sustainable professional development of EFL vocational school teachers and suggestions for further research in this field.